White hot silence - Porter, Henry, 1953- (The Mysterious Press, 2019)
"On a deserted road in Calabria, Greek aid worker Anastasia Cristakos is driving alone to visit one of the new refugee centers funded by billionaire Denis Hisami, whom she has recently married. She slows down to greet two African migrants she recognizes. Too late she realizes they are not her friends. This is an ambush. She manages a desperate phone call to Hisami before her Mafia kidnappers silence her with a powerful drug. Hours later she wakes up in the pitch dark on a container ship, powering eastwards across the Mediterranean. Anastasia has been abducted and is being held hostage because Hisami has explosive information that his enemies have killed for and will kill for again. But Hisami can do nothing to save his wife. His time as a commander with the Kurdish Peshmerga has caught up with him. The U.S. authorities have seized his passport and jailed him for possible terrorist activities in the past. For all his wealth, he is powerless. Only one man can help him. Paul Samson, former MI6 agent and a genius at tracking missing persons. He's the obvious choice. There's only one snag. Samson was, and probably still is, in love with Anastasia. If he manages to locate and save her, will it be for Hisami-or himself?"--